CLIPPINGS AND ABBREVIATIONS IN ENGLISH WORD-FORMATION - Khaydarova Nigora; Makhamadaliyeva Feruza (TADQIQOTLAR, 2025)
Abstract This article explores two important processes in English word-formation: clipping and abbreviation. These methods are part of linguistic economy and are widely used in informal, academic, technical, and digital communication. The paper outlines the types, functions, structural patterns, and usage domains of clippings and abbreviations, illustrating how they contribute to the dynamic development of vocabulary. Through comparison and examples, the study highlights their relevance in modern English and their increasing presence in global linguistic practices.